EXPLORING STUDENTS’ LEARNING STRATEGIES IN READING COMPREHENSION CLASS - Etika Peter; Vivit Rosmayanti; Muhammad Yahrif (Sean Institute, 2023)
This study aims to explore students' learning strategies and their views on the strategies they used to understand reading texts. This study used a qualitative research design by conducting in-depth interviews with two participants who met the criteria set by the researcher. The data collected from the interview were analyzed using qualitative data analysis stages, which are data reduction, data display, and conclusion. The results of this study indicated that the reading comprehension strategies used by students are scamming skimming, previewing, and making an inference. Students perceived that the learning strategy they used was very helpful for them in their daily learning process. In addition, those strategies made it easier for them to do the reading assignments and examinations